Analisis Perilaku Makan Pada Anak Balita Di Desa Jati Rejo Dusun Mawar Kecamatan Pagar Merbau - Dinda Mutiara; Delina Yanti; Rika Halimah; Rani Suraya (CV. ITTC INDONESIA, 2025)
Feeding behaviour in toddlers is very important for physical growth and cognitive development. This study aims to describe the eating patterns of toddlers, influencing factors, and provide recommendations to overcome eating behaviour problems. The method used was descriptive quantitative with a sample of 30 mothers who have children aged 3-5 years in Jati Rejo Village Mawar Hamlet. Data were collected through a structured questionnaire. The results showed that 73.3% of toddlers ate 3-5 times a day and 90% were given food regularly. The foods consumed were varied, but challenges such as picky eating (53.3%) and preference for sweet foods (63.3%) still exist. Family factors, such as nutrition knowledge and shared eating habits, positively influenced children's eating behaviour. This study emphasises the importance of parental education on balanced nutrition and management of picky eating to support children's growth and development.